Does Kinesiophobia Mediate the Relationship between Pain Intensity and Disability in Individuals with Chronic Low-Back Pain and Obesity? - Varallo, Giorgia (Brain Sci, 2021)
Individuals suffering from chronic low-back pain and obesity face severe physical and functional limitations. According to the fear-avoidance model, kinesiophobia might play a crucial role in the relationship between pain intensity and disability. Thus, the purpose of this study was to verify the role of kinesiophobia as a mediator in the association between pain intensity and disability in individuals with both chronic low-back pain and obesity. A total of 213 individuals with chronic low-back pain and obesity were included in the study. The level of kinesiophobia, pain intensity and disability were all assessed using self-reported questionnaires. We verified through a simple mediation analysis that kinesiophobia partially mediated the association between pain intensity and disability in our sample. According to our findings, we emphasize the crucial role of kinesiophobia as a psychological factor that should be addressed in chronic low-back pain rehabilitative protocols to reduce disability in individuals with obesity.